If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 7) = 6(x + 6) Reorder the terms: 7(7 + x) = 6(x + 6) (7 * 7 + x * 7) = 6(x + 6) (49 + 7x) = 6(x + 6) Reorder the terms: 49 + 7x = 6(6 + x) 49 + 7x = (6 * 6 + x * 6) 49 + 7x = (36 + 6x) Solving 49 + 7x = 36 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 49 + 7x + -6x = 36 + 6x + -6x Combine like terms: 7x + -6x = 1x 49 + 1x = 36 + 6x + -6x Combine like terms: 6x + -6x = 0 49 + 1x = 36 + 0 49 + 1x = 36 Add '-49' to each side of the equation. 49 + -49 + 1x = 36 + -49 Combine like terms: 49 + -49 = 0 0 + 1x = 36 + -49 1x = 36 + -49 Combine like terms: 36 + -49 = -13 1x = -13 Divide each side by '1'. x = -13 Simplifying x = -13
| 8m+1=5 | | 5(3x-4)+2x-15=8x+120-3x | | 3*8*9=x | | .08x=.05x+15 | | (-5)+3+18+(-14)= | | 6x+2=3(3+6x) | | (3x-4)+2x-15=8x+120-3x | | a^2-9a-57=-5 | | 1.5ln= | | 8-3k=3k+21 | | log(3)x=log(4)3x | | 9p-4=50+3p | | 3(3-1)+(9)-9= | | a^2+9a+21=7 | | 56/78=13/x | | 9m-24=10+m | | (x-1/6)-(x-3/2)=-1 | | 4x(-6x-2)=32 | | 2x+2=3y | | 0.6667(3p-5)=0.444 | | (3y^2)(ylnx)= | | 7y-(5y-1)=11 | | 7x^2=75 | | 5x+10(2+5)=5x+2 | | 1008=2x-4(x+8) | | 8x+9+5x+15=180 | | (x^2+3x+2y)dx+xdy=0 | | 6k-40=2k | | (6x-5)(x+7)=0 | | 6.5=32.6 | | 2/3b=2-5/6b | | 0.18-0.02(x+3)=0.03(1-x) |